Peningkatan Pemahaman Guru Pendamping Khusus pada Metode Pembelajaran DIR Floortime untuk Siswa Autis: Pengabdian - Ina Agustin; Ifa Seftia Rakhma Widiyanti; Cacik, Sri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service is in partnership with the Kelompok Kerja Guru (KKG) 04 Bima Jaya which includes 6 Elementary Schools, namely SDN Sidorejo 1, SDN Sidorejo 2, SDN Sidorejo 3, SDN Doromukti, SDIT Al Uswah, and SDI Insan Kamil. The number of teachers in KKG 04 Bima Jaya is 108 teachers and 4 autistic children. The target of this community service is the teachers in KKG 04 Bima Jaya. Through this activity, it is hoped that teachers in KKG 04 Bima Jaya will gain increased abilities and skills in the DIR Floortime learning method, so that it can be implemented in students. Autistic students who receive the DIR Floortime learning method are expected to experience improvements in communication and social interaction skills. The results of community service show that teachers in KKG 04 Bima Jaya have increased abilities and skills in the DIR Floortime learning method. Partners will be provided with assistance in developing learning tools using the DIR Floortime learning method for autistic students.